IMPACT OF PYRUVATE CONCENTRATION IN BLOOD ON THE DEVELOPMENT OF POST-PERFUSION CARDIAC FAILURE IN MYOCARDIAL REVASCULIZATION SURGERY WITH CARDIOPULMONARY BYPASS - N. S. Molchan; A. A. Zhloba; Yu. S. Polushin; M. Yu. Shiganov; A. E. Kobak; A. A. Khryapa; I. V. Tretyakova (Вестник анестезиологии и реаниматологии, 2018)
Goal of the study: to evaluate the capability of pyruvate which is endogenously produced during myocardium anoxia to prevent the post-perfusion cardiac failure in the patients undergoing revasculization surgery with cardiopulmonary bypass. Materials and methods. 56 patients with coronary disease who underwent surgery with cardiopulmonary bypass were examined. The samples of blood for anaerobic metabolism tests were collected from the catheter of heart coronary sinus before aortic compression, before release of clamps and in 30 minutes after reperfusion. During the surgery the following rates of hemodynamic profile were registered (cardiac index, systolic output index, medium arterial tension, index of peripheral resistance and pulmonary vessels resistance, index of systolic output of the left and right ventricles, pulmonary capillary wedge pressure), oxygen transportation, consumption and extraction co-efficient, arteriovenous oxygen difference. In the early post-operative period the following rates were evaluated: need in inotropic support, duration of artificial pulmonary ventilation and stay in the intensive care department. The level of troponin I was tested in 12 and 24 hours. Patients were divided into groups depending on the increase of pyruvate level from the start of cardiopulmonary bypass before aortic compression. Group 1 (Pyrx1) included 30 persons with the pyruvate level increase less than twice and Group 2 (Pyrx2) included 26 persons in whom the pyruvate level increased more than twice. No significant differences were found between the groups. Results. Increase of pyruvate concentration in coronary sinus blood does not improve the heart performance in the post-perfusion period. Frequency and speed of consequent regress of post-perfusion heart failure were not principally different in both groups. Post-operative level of troponin I was the same and changed the same manner in both groups. Conclusion. Increased endogenous production of pyruvate in myocardium during anoxia does not improve post-perfusion restoration of the heart function.